Pattern of use of antibiotics in hospitalized patients in the medicine department of a tertiary care hospital - Bai, Muniza; Selvarjan, Sandhiya; Srinivasamurthy, Suresh Kumar; Dutta, Tarun Kumar; Shewade, Deepak Gopal (International Journal of Basic & Clinical Pharmacology, 2016)
Background: (1) To assess pattern of antibiotic use among in-patients of medicine unit in a tertiary care hospital, (2) to determine the frequency of adverse drug reactions (ADR) among the inpatients receiving antibiotics in medicine unit. Methods: The study was prospective and based on the daily review of patient records for 2 months (June, July) of study period, including all the inpatients of medicine unit 1 receiving antimicrobials. The general information of the patients, infection, antimicrobial use, culture and sensitivity reports, concomitant disease, concomitantly administered drugs, as well as clinical response were collected. The prescribed antimicrobials were correlated with the patient’s culture and sensitivity report. The number of defined daily doses (DDDs) administered per patient was calculated for each antimicrobial prescribed as per WHO anatomical therapeutic chemical classification. The ADR observed during the study were assessed using WHO causality analysis. The economic burden of the antimicrobial used was analyzed using average cost of antimicrobial per patient. The study was approved by the Institute Ethics Committee. Results: The antimicrobials that are commonly used as per total drug use (DDDs) are ceftriaxone followed by doxycycline and metronidazole. The antimicrobials account for 58.6% of cost spent on drugs for inpatients. Four antimicrobial related ADR were reported during the study period. Conclusion: Ceftriaxone, doxycycline, and metronidazole are commonly used antibiotics and significant proportion of the cost of drugs is spent for antimicrobials in a medicine unit.